Tingkah laku agresif rusa Timor (Cervus timorensis) jantan di penangkaran pada fase diurnal dan nokturnal - Sally Saurma Silalahi; Daud Samsudewa; Enny Tantini Setiatin; Yon Soepri Ondho (Universitas Sebelas Maret, 2021)
Objective: The aims of this research was known comparison the appearance of aggressive behavior of male Timor deers reared in maintaining females and territories at captivity, between the time of day time (diurnal) and night phase (nocturnal) seen from the duration, frequency, sequence and interval aggresive behavior.Methods: This observational research used the observation focal animal sampling method, by directly observing the aggressive behavior of 4 male Timor deers in a good condition, have hard antlers and maintained at location with the same management and conditions. The duration of observations was 24 hours and carried out for 7 days. The parameters observed included the duration, frequency and interval of aggressive behavior male Timor deers. The data analysis used was the non-parametric statistical test Wilcoxon Signed Rank Test.Results: The results showed that there were significant differences in the four aggressive behavior of Timor deers at day time and nocturnal phase (P <0.20) and the observations showed that the duration and frequency of aggressive behavior Timor deers such as wallowing, walking with head up, shouting, rubbing antlers, threatening, running away and climbing more frequently and for longer periods was shown during the day time (diurnal).Conclusions: Difference time between day time (diurnal) and night phases (nocturnal) causes the duration and frequency aggressive behavior of Timor deers, was longer and more frequent during the day time.